2021
DOI: 10.1002/lt.26273
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to Severe Acute Respiratory Syndrome‐Coronavirus‐2 Messenger RNA Vaccines in Liver Transplant Recipients

Abstract: Prior studies have demonstrated a decreased humoral response in solid organ transplant recipients (SOTRs) to severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) messenger RNA (mRNA) vaccination (17% antibody response after dose 1 [D1], 54% after dose 2 [D2]) compared with the general population (100%).However, these studies were dominated by kidney transplant recipients and included only a small percentage of liver transplantation (LT) recipients (19.6%). (1)(2)(3)(4) Because LT recipients often recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 5 publications
7
67
0
2
Order By: Relevance
“…Forty-seven studies described immunogenicity across various solid organ transplant populations ( n = 5974), mostly in kidney transplant recipients ( n = 3534, 59.2%) ( Table S5 ) [ 18 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , 29 , 34 , 40 , [56] , [57] , [58] ], [ 62 , 63 , 65 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 , 120 , 126 ], [ [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] ]. Twenty-four of those studies included a control group representing overall 1399 participants [ 21 , 34 , 57 , 63 , 66 , 69 , 72 , 73 , 75 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-seven studies described immunogenicity across various solid organ transplant populations ( n = 5974), mostly in kidney transplant recipients ( n = 3534, 59.2%) ( Table S5 ) [ 18 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , 29 , 34 , 40 , [56] , [57] , [58] ], [ 62 , 63 , 65 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 , 120 , 126 ], [ [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] ]. Twenty-four of those studies included a control group representing overall 1399 participants [ 21 , 34 , 57 , 63 , 66 , 69 , 72 , 73 , 75 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Solid organ transplant-specific treatments (calcineurin inhibitors, antimetabolites, corticosteroids) were often associated with a higher non-response rate or lower antibody titres [ 20 , 21 , 24 , 40 , 56 , 62 , 65 , 69 , 72 , 75 , 81 , 136 , [138] , [139] , [140] , [141] , [142] , 144 , 145 , 148 , [154] , [155] , [156] , [157] , 159 , 160 ] ( Table S5 ). Older age and lower estimated glomerular filtration rate were repeatedly associated with a non-responder status [ 21 , 24 , 79 , 120 , 138 , 142 , 144 , 155 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in solid organ transplant recipients that analyzed immunogenicity following 2 doses of COVID-19 mRNA vaccines have demonstrated suboptimal humoral immune response 47 . However, few studies that looked at vaccine efficacy exclusively in LT recipients have shown mixed results 48 , 49 , 50 . One study involving 161 LT recipients (53% received Pfizer and 47% received Moderna) reported a robust immune with 81% of participants producing detectable antibodies 30 days after the second shot 48 .…”
Section: Sars-cov-2 Vaccinesmentioning
confidence: 99%
“… 30 Antibody‐responses ranged between 47.5% 28 and 81%. 31 The efficacy of a third dose of COVID‐19 vaccine has been evaluated in two studies. In a study with 30 patients with suboptimal response, a third dose increased antibody titers in one third of patients who had negative antibody titers and in all patients who had low‐positive antibody titers.…”
Section: Vaccination Of Gi Patientsmentioning
confidence: 99%